1997
DOI: 10.1002/(sici)1097-0215(19970807)72:4<649::aid-ijc17>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targeting of mitomycin C chemotherapy

Abstract: In 10 human cancer cell lines, the activity of mitomycin C (MMC) was found to be determined by an interplay between activation by DT-diaphorase (DTD) and inactivation by glutathione S-transferase (GST). NADPH/cytochrome P-450 reductase was not responsible for MMC activation and expression of MDRI (Mr 170,000 P-glycoprotein), and MRP (multidrug resistance-associated protein) genes did not relate to MMC resistance. Gene expression analysis for NQO1 (DTD gene) and GSTpi predicted which enzyme activity predominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…In this regard, an association between the expression of the dihydropyrimidine dehydrogenase enzyme and 5-fluorouracil resistance in human cancer cells has been demonstrated (Kirihara et al, 1999). Similar findings have been reported for glutathione transferase enzyme activity and resistance to mitomycin C (Singh et al, 1992;Nishiyama et al, 1997). To date only indirect data indicated the presence of CYP3A in healthy colorectal tissue.…”
Section: Discussionsupporting
confidence: 53%
“…In this regard, an association between the expression of the dihydropyrimidine dehydrogenase enzyme and 5-fluorouracil resistance in human cancer cells has been demonstrated (Kirihara et al, 1999). Similar findings have been reported for glutathione transferase enzyme activity and resistance to mitomycin C (Singh et al, 1992;Nishiyama et al, 1997). To date only indirect data indicated the presence of CYP3A in healthy colorectal tissue.…”
Section: Discussionsupporting
confidence: 53%
“…10,[12][13][14][15] The probes used for hybridization were a 3. Electrophoresis and western blot analysis Protein fractions were separated by sodium dodecyl sulfate-polyacrylamide electrophoresis on 7% to 13.5% polyacrylamide gels, followed by transfer to polyvinylidene difluoride membranes for 30 min using a semidry blotting apparatus.…”
Section: )mentioning
confidence: 99%
“…DT-diaphorase plays an important role in activating bioreductive anti-tumour agents like MMC (Begleiter et al, 1989;Ross et al, 1993;Mikami et al, 1996;Nishiyama et al, 1997), EO9 (Plumb   et al, 1994), streptonigrin (Beall et al, 1996) and RH1 (Winski et al, 1998). Cell lines with high levels of DT-diaphorase are more sensitive to MMC (Begleiter et al, 1989;Ross et al, 1993;Mikami et al, 1996), and studies have shown a good correlation between the level of DT-diaphorase activity and the sensitivity to MMC in human tumour cell lines (Fitzsimmons et al, 1996).…”
mentioning
confidence: 99%